The physiological ecology of the steenbras, Lithognathus lithognathus (Teleostei: Sparidae) - Mehl, John A. P (Stellenbosch : Stellenbosch University, 2012)
Thesis (Ph. D.) -- University of Stellenbosch, 1973.